Odpowiedzi

2010-02-10T20:18:52+01:00
2a-3b+3a-2b= 5a+5b
2y-6y+4x-2x=-4y+2x
2x+3-6x-10=-4x-7
-x+2x+(-6)+x-4=2x+10
2ab-6-ab-(-3)=ab-3
3,5b-2,4c-0,6c-0,5b=3b+3c
4 1 4
2010-02-10T20:19:24+01:00
1. 2a-3b+3a-2b = 5a - 5b
2. 2y-6y+4x-2x = -4y + 2x
3. 3x+3-6x-10 = -3x - 7
4. -x+2x+(-6)+x-4 = 2x - 10
5. 2ab - 6 - ab - ( - 3 ) = ab - 3
6. 3,5b - 2,4c - 0,6c - 0,5b = 3 b - 3c
4 1 4
2010-02-10T20:20:46+01:00
2a-3b+3a-2b= 5a-5b
2y-6y+4x-2x= 2x-4y
2x+3-6x-10=4x-7
-x+2x+(-6)+x-4=2x-10
2ab-6-ab-(-3)=ab-3
3,5b-2,4c-0,6c-0,5b=3b-3c

The End ;))
4 1 4